Competenze digitali e educazione: il framework europeo DigComp per proteggersi dall’anti-scienza - Trisolini, Giada (Chimica nella Scuola, 2024)
Is it possible to say that one can protect oneself from anti-science with digital skills? The answer is yes, not only because of the training offered by schools and universities but also because of the numerous European initiatives dedicated to the development of basic digital skills and retraining. This contribution intends to provide an overview of the main funding activated by the EU within the framework of the Year of Competences 2023 aimed at giving a new boost to lifelong learning, taking the European DigComp 2.2 framework and its versions as its main reference.